A Modular Strategy to Engineer Complex Tissues and Organs. Issue 5 (14th February 2018) - Dikina, Anna D.; Alt, Daniel S.; Herberg, Samuel; McMillan, Alexandra; Strobel, Hannah A.; Zheng, Zijie; Cao, Meng; Lai, Bradley P.; Jeon, Oju; Petsinger, Victoria Ivy; Cotton, Calvin U.; Rolle, Marsha W.; et al.
Abstract: Currently, there are no synthetic or biologic materials suitable for long‐term treatment of large tracheal defects. A successful tracheal replacement must (1) have radial rigidity to prevent airway collapse during respiration, (2) contain an immunoprotective respiratory epithelium, and (3) integrate with the host vasculature to support epithelium viability. Herein, biopolymer microspheres are used to deliver chondrogenic growth factors to human mesenchymal stem cells (hMSCs) seeded in a custom mold that self‐assemble into cartilage rings, which can be fused into tubes. These rings and tubes can be fabricated with tunable wall thicknesses and lumen diameters with promising mechanical properties for airway collapse prevention. Epithelialized cartilage is developed by establishing a spatially defined composite tissue composed of human epithelial cells on the surface of an hMSC‐derived cartilage sheet. Prevascular rings comprised of human umbilical vein endothelial cells and hMSCs are fused with cartilage rings to form prevascular–cartilage composite tubes, which are then coated with human epithelial cells, forming a tri‐tissue construct. When prevascular– cartilage tubes are implanted subcutaneously in mice, the prevascular structures anastomose with host vasculature, demonstrated by their ability to be perfused. This microparticle–cell self‐assembly strategy is promising for engineering complex tissues such as a multi‐tissue composite trachea. Abstract : Tissue engineered tracheas with three different tissue types are formed through cellular self‐assembly. Different sizes of cartilage rings and tubes, including native human size, are engineered from mesenchymal stem cell condensations. Prevascular rings are fused with cartilage rings and anastamose with mouse vasculature after subcutaneous implantation. An epithelial lining is developed on the surface of the engineered construct after coculture.